Harmonic cancellation in a Multi-level Inverter Configuration Suitable for PV Applications - Kumar Nallamekala, Kiran; Venkat Raman, K.; Asif, Md. (International Journal of Engineering and Technology, 2018)
Multi-level inverters are playing a major role in PV based systems because of numerous advantages like low dv/dt, better harmonic profile so on. But, conventional multi-level inverters consist of some drawbacks like capacitor balancing issues, greater requirement of capacitor banks and clamping diodes. To address these issues, a novel multi-level inverter has been presented in this paper, which can function as a seven-level, five-level and three-level inverter. The inverter circuit utilizes six switching devices and two isolated DC voltage sources.Â  Moreover, when it is operated as a three-level inverter, a unipolar PWM technique is applied to the circuit which shifts all the lower order harmonics to twice of switching frequency whereas in conventional multi-level inverters, all the harmonics of lower order are present around switching frequency. In addition, proposed inverter can operate even if some switching devices of the circuit fails. Also, the behavior of the inverter during the failure of some switching devices and DC source is analyzed. The proposed inverter is simulated in MATLAB/Simulink and the results are also discussed.Â Â